Characteristics of intracranial atherosclerosis disease in stroke cases in Indonesia utilizing cerebral digital subtraction angiography - Usman, Fritz S.; Kastilong, Merlin P.; Susanto, David; Dafif, Muhammad Welly; Sirait, Gomgom Henrico (International Journal of Research in Medical Sciences, 2024)
Background: Intracranial atherosclerosis disease is a cause of ischemic stroke. Risk factors of ICAD included age, gender, race/ethnicity, hypertension, diabetes mellitus, and dyslipidaemia. This study aimed to describe the profile of ICAD in first-ever stroke and its association of recurrent stroke. Methods: The was a prospective cohort study conducted at a private hospital in Indonesia between January 2021 and June 2022. Inclusion criteria included patients with first-ever stroke and intracranial stenosis confirmed through digital subtraction angiography. The incidence of recurrent stroke was observed at six-month follow-up. Results: Of 40 subjects, 25 (62.5%) were females and most ages ranged from 20 to 40 years old. The prevalent site of intracranial stenosis were internal carotid artery in 19 (23.2%) and anterior cerebral artery in 19 (23.2%) subjects. Following six-month follow-up, there was only a patient with recurrent stroke. Conclusions: In first-ever stroke in Indonesia, ICAD was predominantly described in younger men within 41-60 years old. Stroke recurrence was observed in a patient who was old and had multiple comorbid. Further studies using a larger area and longer duration of follow-up may be considered to provide a more generalized description of ICAD in Indonesia.